Peran Komunikasi dan Organisasi Humas pada Lembaga Pendidikan - Sinaga, Wellty Mely Betesda Br; Gultom, Nur Hidayati; Setiyadi, Bradley (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the role of public relations communication in educational institutions. This research uses various research methods, one of which is library research. Research carried out in libraries using books, journals, previous research and other sources is called library research. The steps for setting goals and the stages of knowing the direction of the target components must be understood by humans before choosing strategies to be used in the classroom. In reality, there are many obstacles that must be overcome in creating public relations communications. Higher education institutions serve as valuable tools for human development and the creation of a better future. Each member of the institution will experience development and change according to the color and pattern of the organization. Public relations can be used to carry out an organization's strategic communications initiatives, but management must fully support public relations. The purpose of this article is to discuss the role of public relations in educational organizations globally. The practice of public relations or public relations has developed and continues to develop, whether consciously or not, as a result of increasingly fierce competition to win public attention. There are many ways used by institutions or companies to explain their programs or policies, even their advantages, but the main goal is to convey them to the public by empowering public relations or public relations, who in this case are tasked with conveying information to the public.